Terapi Komunikasi sebagai Model Pembangun Ketahanan Hubungan Sosial dalam Perkawinan - Pramudibyanto, Hascaryo (Jurnal ILMU KOMUNIKASI, 2009)
Abstract: Many researches show that the conventional marriage counseling to establish marriage relation is not effective. It is indicated by a number of couple has divorced after the counseling. It needs a new counseling method that is more effective. Communication therapeutic is one technique to help the relationship to be stronger. This method offers a good relationship between therapist and client. It means that the therapy must encourage the client and the therapist. The two of them must have a good communication competence so that it creates a communication satisfaction for each. It leads the therapy will be effective to help the marriage relationship.